Arkography : A Grand Tour through the Taken-for-Granted - Olsson, Gunnar, 1935- (Book collections on Project MUSE., 2020)
"Gunnar Olsson's tale follows an explorer from the oldest creation epics extant to the power struggles of today, an attempt to codify the taken-for-granted, a struggle with the invisible powers that make us so obedient and so predictable"--